Research on cross-domain access control technology - Tianyi ZHU; Fenghua LI; Lin CHENG; Yunchuan GUO (网络与信息安全学报)
Based on the latest research at home and abroad, the access control technology in cross-domain data flow were summarized and prospected.Firstly, combined with access control in complex application environments, the development of access control models and data security modelswere summarized.The advantages and disadvantages of access control policy management were analyzed.Secondly, the research on access control policy management from the aspects of data marking, policy matching and policy conflict detection were discussed respectively.Finally, the research status of data marking technology and authorization and extension control technology in unified authorization management were summarized.